1972
DOI: 10.1073/pnas.69.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Encephalomyelitis in Monkeys Induced by a Peptide from the A1 Protein

Abstract: A major disease-inducing site for induction of experimental allergic encephalomyelitis in monkeys exists in Peptide P 14, the 37-residue segment of the Al protein comprising its COOH-terminus. The peptide appears to contain the dominant encephalitogenic determinant, since it was as active as the Al protein on a molar basis. By contrast, the 9-residue tryptophan region and the Peptide R region, active in guinea pigs and rabbits, respectively, were comparatively inactive in monkeys. The clinical and histologic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Two regions, found within the peptide L sequence, have been reported to be more active on a molar basis than peptide L (Figure 6). These peptides have been termed CDl and peptide R (Brostoff et al, 1974;Eylar et al, 1972;Kibler et al, 1972). The CDl peptide was obtained by Brostoff et al (1974) by treatment of the basic protein with cathepsin D. The cathepsin D cleaved the Phe-Phe bond of the basic protein between residues 43 and 44 giving rise to two peptides, CDl and CD2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two regions, found within the peptide L sequence, have been reported to be more active on a molar basis than peptide L (Figure 6). These peptides have been termed CDl and peptide R (Brostoff et al, 1974;Eylar et al, 1972;Kibler et al, 1972). The CDl peptide was obtained by Brostoff et al (1974) by treatment of the basic protein with cathepsin D. The cathepsin D cleaved the Phe-Phe bond of the basic protein between residues 43 and 44 giving rise to two peptides, CDl and CD2.…”
Section: Discussionmentioning
confidence: 99%
“…Since the basic protein contains a single tryptophan residue, it is susceptible to treatment with BNPS-skatole (Omenn et al, 1970), the split product being peptides T and L. Peptide T is a COOH-terminal 54residue peptide which contains one of the monkey sites, whereas peptide L contains two encephalitogenic regions, peptides CD1 and R. On a molar basis peptide L should be more active than peptides T, Y, and M alone. The data obtained so far on peptide L have not supported this interpretation (Eylar et al, 1972) and could be due to the difficulty in obtaining peptide L free from basic protein, since on ion-exchange and gel filtration columns it is eluted close to the basic protein. In the present communication we report the isolation and characterization of peptide L, containing 1% or less of basic protein, which shows weak encephalitogenic activity in the monkey.…”
mentioning
confidence: 87%
“…Unfortunately, these results were not reexamined systematically by these or any other investigators. In 1972 Eylar et al [19] reported that a site in the C-terminal region of BP was active in monkeys. Later, Brostoff et al [8] refer to the 37-residue C-terminal fragment of bovine BP [19] as being "a major encephalitogenic site ... at least 10 times more active than" the site in peptide 45-90 reported by Kibler et al [21].…”
Section: Species-specificity Of Encephalitogenic Sites In Bpmentioning
confidence: 98%
“…In 1972 Eylar et al [19] reported that a site in the C-terminal region of BP was active in monkeys. Later, Brostoff et al [8] refer to the 37-residue C-terminal fragment of bovine BP [19] as being "a major encephalitogenic site ... at least 10 times more active than" the site in peptide 45-90 reported by Kibler et al [21]. In the same paper Brostoff et al [8] also reported that the N-terminal catheptic fragment of bovine BP, residues 1-44, was encephalitogenic in two of three monkeys.…”
Section: Species-specificity Of Encephalitogenic Sites In Bpmentioning
confidence: 98%